Plant, Abiotic Stress and Responses to Climate Change - Andjelkovic, Violeta (IntechOpen, 2018)
Climate change is a serious problem influencing agricultural production worldwide and challenging researchers to investigate plant responses and to breed crops for the changed growing conditions. Abiotic stresses are the most important for crop production, affecting about 96.5% of arable land worldwide. These stress factors include high and low temperature, water deficit (drought) and flooding, salinity, heavy metals, UV radiation, light, chemical pollutants, and so on. Since some of the stresses occurred simultaneously, such as heat and water deficit, causing the interactions of physiological processes, novel multidisciplinary solutions are needed. This book provides an overview of the present state in the research of abiotic stresses and molecular, biochemical, and whole plant responses, helping to prevent the negative impact of global climate change.